2020
DOI: 10.1186/s12913-020-05414-z
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the determinants of health care expenses in emerging economies

Abstract: Background Emerging countries continue to suffer gravely from insufficient healthcare funding, which adversely affects access to quality healthcare and ultimately the health status of citizens. By using panel data from the World Development Indicators, the study examined the determinants of health care expenditure among twenty-two (22) emerging countries from the year 2000 to 2018. Methods The study employed cross-section dependence and homogeneity tests to confirm cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
23
2
Order By: Relevance
“…The estimation results demonstrated that the income elasticity is positive and statistically significant both in the long and the short term. The study confirms the argument that, as a country's income increases, it tends to spend more on population healthcare, which supports the findings of Nghiem and Connelly (2017) and Zhou et al (2020). Income elasticity was estimated to be less than unity, suggesting that healthcare should be regarded as a necessity in CEE countries.…”
Section: Panel Unit Root Tests -Cips and Cadfsupporting
confidence: 87%
See 1 more Smart Citation
“…The estimation results demonstrated that the income elasticity is positive and statistically significant both in the long and the short term. The study confirms the argument that, as a country's income increases, it tends to spend more on population healthcare, which supports the findings of Nghiem and Connelly (2017) and Zhou et al (2020). Income elasticity was estimated to be less than unity, suggesting that healthcare should be regarded as a necessity in CEE countries.…”
Section: Panel Unit Root Tests -Cips and Cadfsupporting
confidence: 87%
“…According to the estimations, infant mortality, as a proxy for advances in medical technology, is negatively related to healthcare spending in the long term (Dreger and Reimers, 2005). Technological advancement, expressed through a decrease in infant mortality, represents a major driving force behind healthcare expenditure growth, which is a finding supported by other studies including those by Zhou et al (2020) and Okunade, You and Koleyni (2018). This suggests that the use of sophisticated procedures and medical treatment can be very expensive, but that such investments are necessary to raise the quality of the healthcare services in CEE countries.…”
Section: Panel Unit Root Tests -Cips and Cadfmentioning
confidence: 70%
“…It is also necessary to emphasise studies that highlight the bidirectional influence between the level of economic development (GDP per capita) and PSH per inhabitant. This research attempts to show how economic development affects PSH, and how investment in people’s health also boosts economic development by enabling people to remain active for longer and in better health [ 70 , 71 , 72 , 73 ]. Moreover, this public investment in health helps to reduce inequalities by limiting and hindering poverty and social exclusion [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates previous evidence showing that out-of-pocket spending for outpatient care increased correlatively with age in Kenya ( 40 ). Additional evidence showed an increase in spending on healthcare among the aged in emerging economies ( 48 ). Thus, the burden of healthcare is higher in households headed by older people.…”
Section: Discussionmentioning
confidence: 99%